(untitled) (Damascus University Journal for legal sciences, 2025)
This research aimed at clarifying the concept of theft in the Torah, its types, punishment, and the wisdom of enacting this punishment. To achieve that, the texts of the Torah, and the sayings of its interpreters were mentioned, studied, and criticised. The relationship between these texts and its religious motive were studied. It was found that the theft’s punishment was limited to the material aspect in most of its cases, and it focused on restoring rights to their owners, without linking verses of theft punishment to the permissible and forbidden, or the punishment of the doomsday for this shameful act.